The Pengembangan Model Pembelajaran MOOC Berbasis Kecerdasan Buatan (AI) untuk Meningkatkan Literasi Digital - Kustiyowati Kustiyowati; Rina Sugiarti Dwi Gita; Annisaa Dwi Ayu Permatasari; Ichwan Zarkasi Brillyano Gunawan (Jurnal Penelitian Pendidikan IPA, 2025)
This study develops and implements a novel Artificial Intelligence (AI)-based MOOCs learning model specifically designed to enhance students’ digital literacy in higher education. Unlike previous studies that focused mainly on content delivery or platform usability, this research integrates adaptive AI algorithms and personalized feedback features into MOOCs to foster more effective and measurable digital literacy development. Using a Research and Development (R&D) approach, the process comprised needs analysis, planning, prototype design, field trials, revisions, and dissemination. The research involved 135 students. Data were collected through observations, questionnaires, interviews, and documentation, and analyzed using both quantitative and qualitative methods. The findings reveal that the AI-based MOOCs model significantly improved students’ digital literacy across all testing phases, with consistent gains shown by the 135 participating students. User feedback confirmed that the model is efficient, adaptive, and practical for classroom application. Furthermore, dissemination activities received a positive response from institutions, lecturers, and students, highlighting its potential for wider adoption. The study concludes that the proposed AI-enhanced MOOCs model provides a scalable and sustainable framework for strengthening digital literacy in higher education, offering empirical evidence for its broader institutional adoption.